PENGARUH PERSEPSI HARGA, INOVASI PRODUK, LOKASI, DAN PROMOSI TERHADAP KEPUTUSAN MEMBELI PROPERTY DI PT. SATYA BALI ARCADIA DENPASAR - M. Rey Lazuardi; I Wayan Sunia; Ni Putu Nina Eka Lestari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Data shows This study aims to determine the influence of price perception, product innovation, location, and promotion on purchasing decisions forproperty at PT. Satya Bali Arcadia Denpasar. The population in this research consists of 1,391 home buyers/customers. Based on the population size, the sampling technique was determined using the Slovin formula. The minimum sample size obtained was 1,391 / (1 + 1,391 (0.1)²) = 93.29, which was rounded up to 94 respondents/customers. The data required for this research include both quantitative and qualitative data, derived from primary and secondary sources. Data collection techniques include documentation, questionnaires, and online data searches. The data analysis techniquesinvolve instrument testing and statistical analysis, with several stages of data analysis, namely: Classical Assumption Tests (Normality Test, Multicollinearity Test, Heteroscedasticity Test), Multiple Linear Regression Analysis, Coefficient of Determination (R²), Partial Significance Test (t-test), and Simultaneous Significance Test (F-test). The results of the study indicate that, partially, there is a positive and significant influence betweenthe price perception variable (X1) and purchasing decisions (Y), with a t-value of 1.197 and a significance level of 0.236. Partially, there is a positive and significant influence between the product innovation variable (X2) and purchasing decisions (Y), with a t-value of 6.370 and a significance level of0.000. Partially, there is a positive and significant influence between the promotion activity variable (X3) and purchasing decisions (Y), with a t- value of 1.331 and a significance level of 0.188. Partially, there is a positive but not significant influence between the business location variable (X4) andpurchasing decisions (Y), with a t-value of 0.487 and a significance level of 0.628. Simultaneously, there is a positive and significant influence among the variables of price perception (X1), product innovation (X2), promotional activities (X3), and business location (X4) on purchasing decisions (Y),with an F-value of 13.093 and a significance level of 0.000.